PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) KANTOR WILAYAH SUMATERA UTARA MEDAN - dr. Nanda Novziransyah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT Human resource management in organizations is means improving human quality for increased performance and organizational outcomes. Realizing an employee discipline and high performance. In improving performance required analysis factors that influence by paying attention to needs of employees as good organization culture and coordinated. Purpose of study to determine influence of organizational culture performance of employees of PT. PLN.Type of research is analytical survey aims to explain influence of variables through a cross-sectional approach. Population was all employees of PT. PLN, amounting 221 people, sample taken with stratified random sampling method to retrieve each field with total sample size 69 people. Analyzed using univariate , bivariate, multivariate at 95% significance level .Results showed that reward system (ρ=0.016) and communication patterns (ρ=0.032), individual initiative (ρ=0.703), tolerance for risk measures (ρ=0.108), directives (ρ=0.098), integration (ρ=0.353), management support (ρ=0.662), control (ρ=0.948), identity (ρ=0.532), tolerance for conflict (ρ=0.336).Suggested to the management of PT PLN (Persero) Regional Office of North Sumatra, Medan to implement the provision of the reward system in accordance with the achievements and more transparency in administration so as to motivate employees to work more productively so as to improve the performance of the company and also implementing the communication patterns of organizations that can provide the necessary information by the employee in performing the task and each section leaders met with the employees so that the employees are motivated to improve their performance. Keywords: Employees, Organizational (Corporate) Culture, Performance.